Influence of Internal and External Governance Mechanisms on Corporate Governance Disclosure among Islamic and Conventional Banks - Rashedul Hasan; Kashfia Sharmeen; Anisa Sultana (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2017)
The purpose of this paper is to investigate the extent of corporate governance disclosure in the annual reports of listed conventional and Islamic banks in Bangladesh. Out of fifty-six scheduled banks in Bangladesh, a sample of thirty-nine banks is selected, and data for the sample is extracted from the annual reports covering a period of 2011 to 2014. As such, the study focused on the extent of CGC after the stock market crisis in 2010 in Bangladesh. This results in the final observations of 116 which were used to perform balanced panel regression analysis. Fixed effect model is found significant for the balanced panel model which indicates that appointment of large audit firms negatively affects the extent of corporate governance compliance. Pooled OLS regression established that while profitability has a negative influence, the size of banks positively affects the extent of CGC. This study has focused on the commercial banks and thus results obtained from the study may not be representative for public and foreign banks operating in Bangladesh. Statistical evidence provided by the study provides guidelines for the policymakers toward necessary governance reforms required for banks to successfully operate in a post-crisis environment. Factors established by the study that influences corporate governance compliance using a balanced panel model are unique in the context of developing countries. Evidence of a difference in governance compliance between Islamic and conventional banks in Bangladesh establishes a new research arena and a necessary shift from the traditional performance comparisons.